2022
DOI: 10.1055/s-0042-1744166
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Sublingual Gland Ranulas

Abstract: Introduction Ranulas are divided into oral (OR) and plunging (PR) and comprise the most common pathology of the sublingual gland. This study presents a case series of patients operated due to OR and PR within different type of modalities in a 1-year period. Objective The aim of this study is to determine the optimal surgical treatment of ranulas based on our results as well as in the literature review. Methods The medical charts of 7 patients with sublingual gland ranulas treated in 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 26 publications
(65 reference statements)
0
26
0
Order By: Relevance
“…WT synchronous with OSCC was found in 17 patients in the included studies. [14][15][16][17][18][19][20][21][22][23][24][25][26] In reported 13 studies, a male preponderance was observed with almost twice as many cases (M: 11, F: 6) [14][15][16][17][18][19][20][21][22][23][24][25][26] with the age ranging between 42 -86 years, and a mean age of 64 years ± (SD). Majority of cases presented with a habit history of tobacco chewing, 14,16,22 smoking, 14,19,[21][22][23][24]26 alcohol consumption.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…WT synchronous with OSCC was found in 17 patients in the included studies. [14][15][16][17][18][19][20][21][22][23][24][25][26] In reported 13 studies, a male preponderance was observed with almost twice as many cases (M: 11, F: 6) [14][15][16][17][18][19][20][21][22][23][24][25][26] with the age ranging between 42 -86 years, and a mean age of 64 years ± (SD). Majority of cases presented with a habit history of tobacco chewing, 14,16,22 smoking, 14,19,[21][22][23][24]26 alcohol consumption.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 96%
“…Thus, 13 articles with full text were logged in for possible inclusion. Thirteen studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and 3 [15,25,26] CS) were finally included in the present review. There were no further studies uncovered in the reference lists of the comprised articles.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations